Enhanced synaptic transmission at the squid giant synapse by artificial seawater based on physically modified saline - Choi, Soonwook; Yu, Eunah; Rabello, Guilherme; Merlo, Suelen; Zemmar, Ajmal; Walton, Kerry D.; Moreno, Herman; Moreira, Jorge E.; Sugimori, Mutsuyuki; Llinas, Rodolfo R. (Frontiers in Synaptic Neuroscience, 2014)
Superfusion of the squid giant synapse with artificial seawater (ASW) based on isotonic saline containing oxygen nanobubbles (RNS60 ASW) generates an enhancement of synaptic transmission. This was determined by examining the postsynaptic response to single and repetitive presynaptic spike activation, spontaneous transmitter release, and presynaptic voltage clamp studies. In the presence of RNS60 ASW single presynaptic stimulation elicited larger postsynaptic potentials (PSP) and more robust recovery from high frequency stimulation than in control ASW. Analysis of postsynaptic noise revealed an increase in spontaneous transmitter release with modified noise kinetics in RNS60 ASW. Presynaptic voltage clamp demonstrated an increased EPSP, without an increase in presynaptic ICa⁺⁺ amplitude during RNS60 ASW superfusion. Synaptic release enhancement reached stable maxima within 5 to 10 minutes of RNS60 ASW superfusion and was maintained for the entire recording time, up to one hour. Electronmicroscopic morphometry indicated a decrease in synaptic vesicle density and the number at active zones with an increase in the number of clathrin-coated vesicles and large endosome-like vesicles near junctional sites. Block of mitochondrial ATP synthesis by presynaptic injection of oligomycin reduced spontaneous release and prevented the synaptic noise increase seen in RNS60 ASW. After ATP block the number of vesicles at the active zone and clathrin-coated vesicles was reduced, with an increase in large vesicles. The possibility that RNS60 ASW acts by increasing mitochondrial ATP synthesis was tested by direct determination of ATP levels in both presynaptic and postsynaptic structures. This was implemented using luciferin/luciferase photon emission, which demonstrated a marked increase in ATP synthesis following RNS60 administration. It is concluded that RNS60 positively modulates synaptic transmission by up-regulating ATP synthesis, thus leading to synaptic transmission enhancement.